Temperatures beyond the community optimum promote the dominance of heat-adapted, fast growing and stress resistant bacteria in alpine soils. (September 2020) - Donhauser, Johanna; Niklaus, Pascal A.; Rousk, Johannes; Larose, Catherine; Frey, Beat
Abstract: Alpine soils are warming strongly, leading to profound alterations in carbon cycling and greenhouse gas budgets, mediated via the soil microbiome. To explore microbial responses to global warming, we incubated eight alpine soils between 4 and 35 °C and linked the temperature dependency of bacterial growth with alterations in community structures and the identification of temperature sensitive taxa. The temperature optimum for bacterial growth was between 27 and 30 °C and was higher in soils from warmer environments. This temperature framing the upper limit of naturally occurring temperatures was a tipping point above which the temperature range for growth shifted towards higher temperatures together with pronounced changes in community structures and diversity based on both 16S rRNA gene and transcript sequencing. For instance, at the highest temperature, we observed a strong increase in OTUs affiliated with Burkholderia-Paraburkholderia, Phenylobacterium, Pseudolabrys, Edaphobacter and Sphingomonas. Dominance at high temperature was explained by a priori adaptation to high temperature, high growth potential as well as stress resistance. At the highest temperature, we moreover observed an overall increase in copiotrophic properties in the community along with high growth rates. Further, temperature effects on community structures depended on the long-term climatic legacy of the soils. These findings contribute to extrapolating from single to multiple sites across a large range of conditions. Highlights: Temperature impacts on alpine soil microbiome depend on climatic legacy of the soil. Strong temperature effects above community optimum for growth, minor effects below. High bacterial growth rates and copiotrophic features at high temperature. High temperature promotes heat-adapted, stress resistant and fast growing bacteria. Burkholderia, Phenylobacterium, Pseudolabrys and Edaphobacter favored by heat.